2018
DOI: 10.1177/1040638718793677
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of density gradient ultracentrifugation serum lipoprotein profiles in healthy dogs and dogs with exocrine pancreatic insufficiency

Abstract: Changes in proportions of lipoprotein classes have been described in disease states in humans. In veterinary medicine, hyperlipidemia can cause complications, such as cutaneous xanthomas, liver disease, cholelithiasis, pancreatitis, glomerular disease, lipemia retinalis, or peripheral neuropathy, but there are few reports regarding lipoproteins in diseased animals. For canine serum, we partially validated continuous lipoprotein density profiling (CLPDP), a novel density gradient ultracentrifugation technique. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Lipoprotein profiling was carried out using a bismuth sodium ethylenediaminetetraacetic acid (NaBiEDTA) density gradient ultracentrifugation method as previously described . This method has been validated in dogs and used to evaluate lipoprotein profiles in healthy dogs and in dogs with idiopathic hyperlipidemia and exocrine pancreatic insufficiency . This method also has been used to evaluate lipoprotein profiles in cats with hepatic lipidosis .…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Lipoprotein profiling was carried out using a bismuth sodium ethylenediaminetetraacetic acid (NaBiEDTA) density gradient ultracentrifugation method as previously described . This method has been validated in dogs and used to evaluate lipoprotein profiles in healthy dogs and in dogs with idiopathic hyperlipidemia and exocrine pancreatic insufficiency . This method also has been used to evaluate lipoprotein profiles in cats with hepatic lipidosis .…”
Section: Methodsmentioning
confidence: 99%
“…The methodology used in our study previously was shown to identify 11 distinct lipoprotein fractions in dogs based solely on density characteristics . Because the functional characteristics and composition of most lipoprotein density subfractions in dogs currently are unknown, all density subfractions can only be nominally assigned to traditional functional classes such as low‐density lipoproteins (LDL) or high‐density lipoproteins (HDL).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations